Immunomodulatory peptide–drug conjugate MEL-dKLA suppresses progression of prostate cancer by eliminating M2-like tumor-associated macrophages - Han, Ik-Hwan; Choi, Ilseob; Kim, Soyoung; Kwon, Minjin; Choi, Hyojung; Bae, Hyunsu (Frontiers in Immunology, 2025)
Prostate cancer is one of the most common malignancies in men and is frequently associated with tumor-promoting inflammation. Tumor-associated macrophages (TAMs) are known to facilitate cancer progression by suppressing antitumor immunity. Therefore, targeting TAMs represents a promising strategy for cancer therapy. This study aimed to investigate whether melittin-dKLA, a conjugated peptide consisting of melittin (MEL), which selectively binds M2-like macrophages, and the pro-apoptotic peptide d(KLAKLAK)2 (dKLA), can inhibit prostate cancer progression by targeting M2 macrophages. Human monocytic cells (THP-1 cells) were differentiated into TAMs using tumor-conditioned medium (TCM), and the conditioned medium from these TAMs was termed M-TCM. MEL-dKLA binding affinity was assessed using FITC-labeled melittin. A prostate cancer mouse model was established by subcutaneous injection of TRAMP-C2 cells, followed by MEL-dKLA administration every three days. As a result, THP-1-derived macrophages stimulated with TCM exhibited elevated expression of M2 markers (ARG1, CD206, and CD163). Prostate cancer cells (PC-3) stimulated with M-TCM showed increased proliferation and expression of epithelial-mesenchymal transition (EMT) markers. MEL-dKLA preferentially bound to M2 macrophages and TAMs, and inducing selective cytotoxicity. Conditioned media from MEL-dKLA-treated M2 macrophages and TAMs resulted in markedly decreased PC-3 cell proliferation, migration, and invasion. In vivo, MEL-dKLA treatment significantly reduced tumor growth, decreased the number of CD163+ M2 macrophages, and increased CD8+ T cell infiltration in tumor tissues. These findings demonstrate that MEL-dKLA suppresses prostate cancer progression by targeting M2-like TAMs both in vitro and in vivo. MEL-dKLA may serve as a promising therapeutic agent to modulate the tumor microenvironment in prostate cancer.